Efficacy of oral versus intravenous steroids in the treatment of pediatric immune thrombocytopenic purpura: A single center experience - Abdullah Essam Ahmed; Akram Nabeeha Najatee (Acta Marisiensis - Seria Medica, 2025)
Objectives: This study conducted to assess the response rate to steroid in children with acute primary ITP and compare the relative effectiveness of oral steroid to intravenous dexamethasone.